Long-Term Clinical and Immunological Profile of Kidney Transplant Patients Given Mesenchymal Stromal Cell Immunotherapy - Perico, Norberto; Casiraghi, Federica; Todeschini, Marta; Cortinovis, Monica; Gotti, Eliana; Portalupi, Valentina; Mister, Marilena; Gaspari, Flavio; Villa, Alessandro; Fiori, Sonia; Introna, Martino; Longhi, Elena; et al. (Frontiers in Immunology, 2018)
We report here the long-term clinical and immunological results of 4 living-donor kidney transplant patients given autologous bone marrow-derived mesenchymal stromal cells (MSC) as part of a phase 1 study focused on the safety and feasibility of this cell therapy. According to study protocols implemented over time, based on initial early safety findings, the patients were given MSC at day 7 post-transplant (n=2) or at day-1 pre-transplant (n=2) and received induction therapy with basiliximab and low-dose Rabbit Anti-Thymocyte Globulin (RATG) or RATG alone, and were maintained on low-dose ciclosporin (CsA)/mycophenolate mofetil (MMF). All MSC-treated patients had stable graft function during the 5-7 year follow-up, without increased susceptibility to infections or neoplasm. In 3 MSC recipients, but not historical control patients, circulating memory CD8+ T cell percentages remained lower than basal, coupled with persistent reduction of ex-vivo donor-specific cytotoxicity. Two patients showed a long-lasting increase in the Treg/memory CD8+ T cell ratio, paralleled by high circulating levels of naïve and transitional B cells. In one of these two patients CsA was successfully discontinued and currently the low-dose MMF monotherapy is on the tapering phase. The study shows that MSC therapy is safe in the long-term and could promote a pro-tolerogenic environment in selected patients. Extensive immunomonitoring of MSC-treated kidney transplant recipients could help selection of patients for safe withdrawal of maintenance immunosuppressive drugs (NCT00752479 and NCT02012153).